Assessing soil properties under prominent agroforestry systems in temperate Himalayan region - Saleem, Ishrat; Mugloo, J. A; pala, nazir A.; Khan, P. A; Bhat, G.; Arjumand, Tahera (Indian Journal of Agroforestry, 2023)
Agroforestry systems has significant effect on soil properties which are the most important indicators of soil health. As one of the primary sources of carbon sequestration on earth, soil health is the most basic asset for the ecosystem wellbeing and sustainability. The present study was carried out to assess soil acidity, electric conductivity, organic carbon, and nutrient status (N, P, K) in four prominent agroforestry systems viz., horti-agriculture, boundary plantation, homegardens and horti-silvipasture in temperate conditions of Kashmir Himalaya. Horti-silvipasture system showed higher values of soil electric conductivity, organic carbon and available N, P, K than other agroforestry systems. A maximum value of soil electric conductivity (0.32 dS/m), organic carbon (1.55%) and available N, P, K as 313.6 kgha-1, 39.6 kgha-1 and 292.1 kgha-1 respectively was observed in horti-silvipasture followed by agri-hortisilviculture (homegardens), horti-agriculture and agri-silviculture (boundary plantation). Also, highest value (7.05) of pH was recorded in agri-silviculture (boundary plantation) and lowest (6.76) in horti-silvipasture system. Soil electric conductivity, organic carbon and available N, P, K shows a decreasing trend and soil reaction (pH) shows an increasing trend as we move downwards depth wise. Thus, all the studied tree-based land use systems at temperate zones were found as sustainable because of efficient nutrient cycling and played an important role in carbon mitigation and need to be protected and promoted on a large scale. The findings of this paper will aid in persuading farmers to embrace agroforestry methods on a wide scale.